Os conectores em função da escrita: conectando memórias - Silva, Helena Tavares Viana da (2023)
One of the great difficulties presented by students in writing is the connection between the sentences in the text, as they often make up a cluster of ideas. Therefore, it is necessary to practice language teaching whose focus is on connectors that play the role of connection in the text.For that, this research proposes a suggestion for teaching connectors as resources capable of establishing semantic-discursive relationships between terms, clauses and linguistic periods, based, above all, on Antunes (2005) and Koch (2018). In order to have a genre as the focus of this language teaching perspective is based on Bakhtin's theory (1997), according to which the use of language occurs through utterances, that is, the speech genres, among which there was a choice for the memoir genre. Thus, the 8th grade students of a municipal school in João Pessoa wrote memoirs reported by residents of the Mangabeira neighborhood, in which the referred school is located. The main theme of these reportsis from the commerce of this neighborhood, which is linked to its history. It was defined as a general objective to encourage students to write cohesive texts, especially establishing semantic-discursive relationships between clauses, sentences and paragraphs. These being the specific objectives: situate the study of the text in Textual Linguistics; present the importance of cohesion for written production, especially regarding the connectors that establish semantic-discursive relationships between clauses, sentences and paragraphs; record memories of the trade in Mangabeira through memoir reports written by students, based on interviews with residents of the neighborhood; develop a pedagogical notebook contemplating a methodological proposal that contributes to the teaching of connectors that establish semantic-discursive relationships in the textual production of memoir reports. For this purpose, it was developed a qualitative research supported by Esteban (2010), whose form of fieldwork was an interventionist action research, about which Paiva (2019) presents some theories. In order to carry out a study of the existing literature on the subject discussed it was used the methodological procedure of the bibliographic review, with reading in Alves-Mazzotti and Gewandsznajder (2004), which was essential to then proceed with the generation of data, which was made from a didactic sequence, based on Dolz, Noverraz and Schneuwly (2004). Once the data was generated, they were described through content analysis, based on Bardin (2011). Finally, a pedagogical notebook will be prepared, as the final product of the research, with the aim of offering Portuguese language students in Elementary School a proposal for teaching connectors as resources that establish semantic-discursive relationships in memoir reports. Through this path, the expected results were achieved: the production of memory reports in which connectors were used, as well as learning, throughout the process, about textual organization and many other aspects involved in the didactic sequence.